Exigibilidad de los derechos económicos, sociales y culturales de las comunidades indígenas en la provincia de Zamora Chinchipe - Ludeña Orellana, Andrea Alexandra (2014)
This research focuses on the "Enforceability of economic, social and cultural rights of the province of Zamora Chinchipe", which presents the results of a research process of economic, social and cultural rights of the indigenous communities of Zamora Chinchipe only the Shuar communities. Here the living conditions of the indigenous Shuar communities in different territories where they are seated show, so we could detect through interviews and observation, that the State through various levels of governments have invested little to improve the quality of life of the inhabitants of indigenous communities. Health and basic services where less attention from the state has, just as in education and communication these rights are enshrined in the constitution where it must respect and ensure the effective implementation, but in practice it is not because these communities have little care and concern for the state to guarantee the rights they deserve